The Impact of Using Artificial intelligence on Auditors Performance in Saudi Business Environment - Al-Salem, Kawthar Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the impact of artificial intelligence (AI) on the performance of Saudi auditors in the Saudi business environment based on three principles: identifying fundamental errors, adherence to systems and regulations, and the organization's ability to sustain. The study community consisted of all licensed audit firms in the Kingdom of Saudi Arabia, and the sample size was 162 firms. To achieve the study's objectives, the descriptive survey method was used, relying on questionnaires as the primary data collection tool. The study found a positive impact of AI on the performance of auditors in reviewing the financial statements of Saudi joint-stock companies. AI has increased auditors' ability to detect fundamental errors significantly (average response: 4.27, standard deviation: 0.8226). Additionally, AI has facilitated the detection of non-compliance by auditors with regulations (average response: 4.18, standard deviation: 0.8506). Furthermore, AI has had a positive impact on auditors' evaluation of management's ability to sustain (average response: 4.23, standard deviation: 0.8114). The researcher recommends several suggestions, including enhancing digital infrastructure to pave the way for the use of AI technologies in the future and the need to develop the audit process to meet the profession's requirements and keep up with the latest technological developments.
Keywords: Artificial intelligence; Auditors; Saudi Business Environment